2016
DOI: 10.1108/ijcst-08-2015-0086
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort properties of bamboo tencel knitted fabrics

Abstract: Purpose – The purpose of this paper is to present the thermal comfort properties of single jersey knitted fabric structures made from bamboo, tencel and bamboo-tencel blended yarns. Design/methodology/approach – Bamboo, tencel fibre and blends of the two fibres were spun into yarns of identical linear density (30s Ne). Each of the blended yarns so produced was converted to single jersey knitted fabrics with loose, medium and tight struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…It was observed that the air permeability and water vapor permeability were increased with the increase of tencel lyocell. One-hundred-percent tencel lyocell fabrics gave more thermal resistance and air permeability compared with bamboo rayon/tencel lyocell–blended fabrics (Karthikeyan, Nalankilli, Shanmugasundaram, & Prakash, 2016). Moreover, the cotton and bamboo rayon blended knits using rotor-spun yarns were examined, which showed that 50/50 cotton and bamboo rayon blended knitted fabrics had comparable comfort properties with respect to 100% bamboo rayon fabrics (Majumdar & Pol, 2014; Ramakrishnan, Umapathy, & Prakash, 2015).…”
mentioning
confidence: 99%
“…It was observed that the air permeability and water vapor permeability were increased with the increase of tencel lyocell. One-hundred-percent tencel lyocell fabrics gave more thermal resistance and air permeability compared with bamboo rayon/tencel lyocell–blended fabrics (Karthikeyan, Nalankilli, Shanmugasundaram, & Prakash, 2016). Moreover, the cotton and bamboo rayon blended knits using rotor-spun yarns were examined, which showed that 50/50 cotton and bamboo rayon blended knitted fabrics had comparable comfort properties with respect to 100% bamboo rayon fabrics (Majumdar & Pol, 2014; Ramakrishnan, Umapathy, & Prakash, 2015).…”
mentioning
confidence: 99%
“…Karthikeyan et al (2016) 3 avowed that thinner fabrics be evidence for faster wetting than thicker ones, when equal amounts of water are applied. Moreover, as the bamboo and modal yarns had lower bending rigidity, the knitted loops in the fabric can be compressed more easily and result in lower fabric thickness, a finding that also contributes to the lower wetting time of the bamboo and modal knitted fabrics (Prakash et al 2013) 4 . Hence it can be concluded that the wetting time values for both top and bottom surfaces has increased after dyeing in all cases this may be due to fabric set.…”
Section: Figurementioning
confidence: 99%
“…From table (7) and figure (6) it is obvious that the air permeability also tends to increase with the increase of the loop length as expected. Where the loop length increases, the compactness of the fabrics decreases due to the decrease in the number of stitches (15) .…”
Section: ‫والفنون‬ ‫العمارة‬ ‫مجلة‬ ‫ا‬ ‫ال‬ ‫لعدد‬ ‫ثامن‬ ‫عشر‬mentioning
confidence: 99%